Glycodendron–rhenium complexes as luminescent probes for lectin sensing. Issue 37 (18th September 2018) - Palmioli, Alessandro; Panigati, Monica; Bernardi, Anna
Abstract : Enhanced emission intensity of novel Re(i )-glycoprobes resulting from the specific recognition of carbohydrate-binding proteins as a potential tool in bioimaging applications. Abstract : The design, synthesis and characterization of novel glycoconjugate luminescent probes based on dinuclear rhenium(i ) complexes are reported. A multivalent platform bearing different carbohydrate moieties (Glc, Gal and Man) was used to target carbohydrate-binding proteins (lectins), exploiting the unique photophysical characteristics of a Re(i ) luminophore for protein sensing. Our results show that these glycoconjugates, non-luminescent in aqueous medium, are able to specifically bind different lectins (ConA and PNA) with a consequent enhancement of emission intensity. These findings suggest the use of Re(i )-based glycoconjugates as switch-on luminescent probe tools in biological applications.